Pengaruh Komunikasi Interpersonal, Pelatihan, dan Sikap Kerja Terhadap Kinerja Pegawai - Wanda Frenawan; Anderson Juang Situmorang; Asriani Hutabarat; Anggiat Aloysius Sinaga; Friska Rumondong Hutagalung; Supar Wasesa; Safrida Safrida; T. Ahmad Helmi; Sri Rahayu; Neni Sri Wahyuni (TIN: Terapan Informatika Nusantara, 2023)
This study aims to determine the effect of interpersonal communication on employee performance in the work environment of the East Aceh District National Land Agency with 29 employee respondents. This type of research is field-based using a quantitative approach. In this study the authors used a quantitative and associative approach. Data collection techniques in this study used library study techniques and questionnaire techniques. The results showed: 1) Interpersonal communication has a positive and significant effect on employee performance. This is evidenced by the coefficient value tcount<ttable, which is 3.490<1.703 at 0.002<0.05 significant. It is concluded that hypothesis H is rejected and H1 is accepted. 2) Training has a positive and significant effect on employee performance. This is evidenced by the coefficient value of tcount>ttable, which is 3.769>1.703 at a significant 0.001<0.05. It can be concluded that hypothesis H is rejected and H1 is accepted. 3) work attitude has a positive but not significant effect on employee performance. This is evidenced by the value of the coefficient tcount>ttable, which is 0.004<1.703 at a significant 0.960>0.05. which concluded that the research hypothesis H3 was rejected and H0 was accepted. 4) Simultaneously interpersonal communication, job training and work attitudes have a positive effect on improving employee performance. Which is based on the results of the study using the F test (simultaneous test) with a significant value of α 0.000 <0.05 and the value of Fcount > Ftable (68.382> 3.35). The magnitude of the coefficient of determination (R Square) is R Square 0.878 or equal to 87.8%. This figure implies that the variables Interpersonal Communication (X1), Training (X2), Work Attitude (X3) simultaneously affect the Employee Performance variable (Y) of 87.8%. And the rest (100% -87.8% = 12.2%) is influenced by other variables outside the regression equation or the variables studied.